Therapeutic Drug Monitoring (TDM) Teofilin sebagai Antiasma di Indonesia - Elizabeth, Maria; Rusdiana, Taofik (Jurnal Farmasi & Sains Indonesia, 2023)
Therapeutic Drug Monitoring (TDM) is a clinical pharmacy service aimed at increasing the effectiveness of therapy and improving patient safety. TDM is widely used in the use of drugs with a narrow therapeutic index or can cause toxic effects in small dose changes, such as theophylline. Theophylline is a xanthine class of drugs which is still often used in Indonesia and has a bronchodilatory effect so that it can be used in the treatment of asthma or chronic obstructive pulmonary disease (COPD). This drug has a narrow therapeutic index with a therapeutic dose of between 10-20 mg/L, concentrations above 20 mg/L can cause dangerous side effects such as nausea, vomiting, metabolic acidosis, gastrointestinal bleeding, and even death. Theophylline is one of the drugs that needs to be monitored related to the improvement of symptoms and drug levels in plasma. Therefore, the purpose of writing this article is to look at theophylline monitoring that has been carried out in Indonesia with a literature study approach using inclusion and exclusion criteria. The results obtained are that there are still a few hospitals that carry out therapy drug monitoring related to theophylline levels in the blood.